“IF MY MOTHER WERE STILL ALIVE, I AND YOU WOULD DEFINITELY GET DIVORCED”: A CASE STUDY OF A VIETNAMESE WOMAN’S REFUSING IN INTERACTION - Du, Nguyen Trong (VNU Journal of Foreign Studies; Vol 35 No 1DO - 10.25073/2525-2445/vnufs.4335, 2019)
This paper presents the major findings from a recent study conducted to explore how a Vietnamese woman refuses a high-stakes advice or request in everyday conversations. Data used in this study are conversations excerpted from a TV series entitled Những công dân tập thể (lit. the citizens living in the same apartment building). The analytical tool is a combination of Conversation Analysis (Hutchby & Wooffitt, 1998, 2008; Sacks, 1992a, 1992b) and Multimodal Interactional Analysis (Norris, 2004, 2009). The results show that (1) Vietnamese refusing is often performed concurrently by different modes of communication and language is only one of them; (2) refusing a high-stakes advice or request often takes a long time to negotiate in a conversation and through a series of conversations; and (3) Vietnamese women’s responsibility to obey their parents, a Confucian teaching, still has its role in contemporary Vietnamese society.